2015
DOI: 10.1093/pubmed/fdv053
|View full text |Cite
|
Sign up to set email alerts
|

A process evaluation of the NHS Health Check care pathway in a primary care setting

Abstract: Disparities in uptake and implementation of the care pathway demonstrate inconsistencies in the application of processes and knowledge. There appears to be an overestimation of CVD risk by the Ready Reckoner tool likely to be attributable to a failure to adjust for existing local early identification efforts in primary care and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…38 Nine further studies reported data on coverage (Table 1). 13,18,[21][22][23][24][29][30][31] Reported coverage. The PHE website reported coverage of 45.6% for the whole of England (2013-2014 to Q2, 2016-2017), ranging from 18.9% in Surrey to 109.2% in Newham.…”
Section: Coverage (N = 10)mentioning
confidence: 99%
“…38 Nine further studies reported data on coverage (Table 1). 13,18,[21][22][23][24][29][30][31] Reported coverage. The PHE website reported coverage of 45.6% for the whole of England (2013-2014 to Q2, 2016-2017), ranging from 18.9% in Surrey to 109.2% in Newham.…”
Section: Coverage (N = 10)mentioning
confidence: 99%
“…quantitative measurements to assess the size, shape and composition of patients), and providing lifestyle advice (McNaughton et al, 2011). While evidence is emerging concerning patient perceptions of HCs (Baker et al, 2015;Burgess et al, 2014;Ellis et al, 2015;Ismail & Atkin, 2015;Jenkinson et al, 2015), there is a lack of evidence concerning health professionals' experiences and perspectives of the programme. The aim of this study was to investigate health professionals' experiences and perspectives concerning the implementation of a local HC programme and challenges to delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In Great Britain, pharmacists have a role in primary care teams, and provide valuable services that have been accepted by the public, such as medication use reviews and cardiovascular screenings . However, limitations to the system are found in such areas as the budget squeeze, competition and supply chain pressures, consumer demands, inconsistency of services provided, unacceptable appointment management, insufficient follow‐up advice, and time pressures when there are not enough pharmacists available to deliver services …”
Section: Discussionmentioning
confidence: 99%
“…[54,55] However, limitations to the system are found in such areas as the budget squeeze, competition and supply chain pressures, consumer demands, [11,56] inconsistency of services provided, unacceptable appointment management, insufficient follow-up advice, and time pressures when there are not enough pharmacists available to deliver services. [54,57]…”
Section: Discussionmentioning
confidence: 99%